One-step synthesis of rice husk carbon with dangling CC bonds loaded g-C3N4 for enhanced photocatalytic degradation. (1st November 2020) - Wen, Xue; Wang, Wenqiang; Ye, Qiuping; Zhou, Yunfei; Yang, Jian; Sun, Na; Tan, Yigen; Wang, Wenbin; Hou, Yang; Yan, Chunjie
Abstract: Metal-free graphitic carbon nitride (g-C3 N4 ) should be an ideal candidate for photocatalytic degradation of pollutants. However, its performance is limited by low adsorption and high recombination rate of electron-hole pairs. Herein, g-C3 N4 nanosheets were highly dispersed on rice husk carbon (CN@RHC) by one-step sealed calcination. The specific surface area was greatly increased from 7.7 to 137 m 2 /g, which improves the adsorption performance. Abundant dangling CC bond defects of rice husk carbon were confirmed by electron paramagnetic resonance, which played an important role of electron acceptor and effectively inhibit the recombination of photogenerated carriers. As a result, 98% of Methylene blue was removed in 4.5 h using a 5 W light emitting diode source with visible light while only 80% of that was removed by bulk g-C3 N4 . The degradation performance was enhanced by the synergism of excellent adsorption performance and better photogenerated carriers transport performance. Based on the simple synthesis method, low cost and excellent visible photocatalytic performance, dangling CC bonds should be the focus for promoting photocatalysis as well as improve the added value of agricultural waste. Graphical abstract: Image 1 Highlights: g-C3 N4 nanosheets were highly dispersed on rice husk carbon via one-step sealed calcination. The removal rate of methylene blue increased from 80% to 98%. The influence of dangling CC bond defects on the photocatalytic degradation was discussed for the first time.